STUDY OF FLAVONOIDS AND BIOELEMENTS CONTENT IN THE AERIAL PART OF TARAXACUM OFFICINALE WIGG. S.L., GROWING IN SOUTHERN FERGANA (Scientific journal of the Fergana State University, 2025)
For the first time, using the HPLC method and instrumental neutron activation analysis was studied the quantitative composition of 6 flavonoids and 38 macro- and microelements in the above-ground parts of Taraxacum officinale Wigg. s.L. growing in the territory of Southern Fergana. It was established that composition of Taraxacum officinale Wigg. s.L. dihydroquercetin predominates (25.2 mg/g), macro- and microelements Na (920 mg/kg), Ca (38700 mg/kg), Fe (2970 mg/kg), Mn (94.5 mg/kg) and Cu (15 mg/kg). The amount of toxic elements in the composition of all the studied plants does not exceed the maximum permissible concentration.